"They don't Know Better than I do": People Prefer Seeing for Themselves Over Using the Wisdom of Crowds in Perceptual Decision Making. Issue 1 (21st June 2021) - Yonah, Merav; Kessler, Yoav
Establishing the way people decide to use or avoid information when making a decision is of great theoretical and applied interest. In particular, the "big data revolution" enables decision-makers to harness the wisdom of crowds (WoC) toward reaching better decisions. The WoC is a well-documented phenomenon that highlights the potential superiority of collective wisdom over that of an individual. However, individuals may fail to utilize the power of collective wisdom as a means for optimizing decision outcomes. Using a random dot motion task, the present study examined situations in which decision-makers must choose between relying on their personal information or relying on the WoC in their decision. Although the latter was always the reward-maximizing choice, a substantial part of the participants chose to rely on their own observation and also advised others to do so. This choice tendency was associated with higher confidence, but not with better task performance, and hence reflects overconfidence. Acknowledging and understanding this decision bias may help mitigating it in applied settings.